Hafnium-tungsten chronometry of angrites and the earliest evolution of planetary objects - Markowski, A; Quitte, G; Kleine, T; Halliday, A; Bizzarro, M; Irving, A (2007)
Angrites are amongst the oldest basalts in the solar system and their origins are enigmatic, some even proposing the planet Mercury as the parent body (APB). Whatever their exact provenance their chronometry provides insights into early stages of planetary melting and differentiation. We present the first high-precision internal 182Hf- 182W isochrons for such early differentiated objects. Angrites Sahara 99555, D'Orbigny, and Northwest Africa 2999 define ages of 5.1 ± 1.3 Ma, 4.7 ± 1.3 Ma and 9.5 ± 3.3 Ma respectively after formation of calcium-aluminum-rich refractory inclusions (CAIs). These data are in good agreement with 26Al- 26Mg, 53Mn- 53Cr and most 207Pb- 206Pb ages for other angrites and provide evidence for two texturally and temporally well-resolved groups. The quenched angrites (SAH 99555, D'Orbigny and five others) have a weighted mean age of 4562.1 ± 0.4 Ma and are the products of igneous crystallization on the APB ∼ 5 Ma after the formation of CAIs, whereas the more slowly cooled angrites (NWA 2999, Angra dos Reis, LEW 86010, average age: 4557.7 ±0.2 Ma) reflect metamorphic closure ∼ 5 Ma later following second reheating process or a complex cooling history. The concordance obtained between various short-lived chronometers provides evidence that 26Al, 53Mn and 182Hf were homogeneously distributed in the solar nebula, although we cannot rule out the possibility of local small heterogeneities. Contrary to recent proposals, the data are also consistent with the previously determined age of the solar system based on 207Pb- 206Pb systematics of CAIs. The Hf-W data are discussed in the context of two endmember models for the early differentiation of the angrite parent body. In the first model, core formation occurred at 3-4 Ma after CAIs and both groups of angrites formed by two distinct partial melting events from the bulk mantle of the angrite parent body. In the second model, the angrite parent body underwent progressive core formation with an increasing degree of W-depletion over time. In this model, the two groups of angrites derive from distinct reservoirs. The heat sources responsible for such late melting and core formation are unclear. Quenched angrites are coeval with non-magmatic IAB iron meteorites and CB chondrules at ∼ 4562 Ma. However, demonstration of a genetic link between angrite melting and impact events must await the acquisition of still higher resolution chronometry. © 2007 Elsevier B.V. All rights reserved.